Development of a dual‐label time‐resolved fluoroimmunoassay for the detection of α‐fetoprotein and hepatitis B virus surface antigen. (20th June 2012) - Lin, Guan‐Feng; Liu, Tian‐Cai; Zou, Li‐Ping; Hou, Jing‐Yuan; Wu, Ying‐Song
ABSTRACT: Time‐resolved fluorometry of lanthanide chelates is one of the most useful non‐isotopic detection techniques and has been used in numerous applications in biomedical science. We developed a time‐resolved fluoroimmunoassay (TRFIA) to quantify α‐fetoprotein (AFP) and hepatitis B virus surface antigen (HBsAg) in human serum. Based on a two‐site sandwich protocol, monoclonal antibodies (McAbs) against AFP and HBsAg were co‐coated in 96 microtitration wells and tracer McAbs against HBsAg and AFP were labeled with europium (Eu) and samarium (Sm) chelates, respectively. After application of diluted serum samples, Eu 3+ ‐ and Sm 3+ ‐McAbs were added and fluorescence signals of Sm 3+ and Eu 3+ tracers were collected. Detection limits of AFP and HBsAg were 0.09 mIU/L and 0.01 µg/L, respectively. Measurement ranges of AFP‐TRFIA and HBsAg‐TRFIA were 1–1000 mIU/L and 0.2‐150 µg/L, respectively. Intra‐ and inter‐assay coefficients of variation of AFP‐TRFIA were 3.3‐4.1% and 5.7‐7.2% and for HBsAg‐TRFIA were 2.9‐3.9% and 4.9‐6.8%, respectively. Linear correlation of TRFIA and chemiluminescence immunoassay measurements resulted in a correlation coefficient of 0.9949 for AFP and 0.9940 for HBsAg. For the endurance test, Eu‐labeled McAbs were stable for at least one year at −20°C and the results of the TRFIA with the same reagents were also reproducible after one year. The availability of a highly sensitive, reliable and convenient AFP/HBsAg TRFIA will allow the quantification of both AFP and HBsAg, thereby providing diagnostic value in various clinical conditions and could be applied for clinical use. Copyright © 2012 John Wiley & Sons, Ltd.